2021
DOI: 10.3390/genes12010064
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Recurrent Pregnancy Loss in the Ukrainian Population Using a Combined Effect of Genetic Variants: A Case-Control Study

Abstract: We assessed the predictive ability of a combined genetic variant panel for the risk of recurrent pregnancy loss (RPL) through a case-control study. Our study sample was from Ukraine and included 114 cases with idiopathic RPL and 106 controls without any pregnancy losses/complications and with at least one healthy child. We genotyped variants within 12 genetic loci reflecting the main biological pathways involved in pregnancy maintenance: blood coagulation (F2, F5, F7, GP1A), hormonal regulation (ESR1, ADRB2), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…A multilocus genetic approach, by selecting those SNPs previously shown to be significantly associated with thrombosis and/or with pregnancy-related thrombosis in GWAS or large multicenter studies, could reveal if additional molecular markers had a role in this peculiar clinical finding [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multilocus genetic approach, by selecting those SNPs previously shown to be significantly associated with thrombosis and/or with pregnancy-related thrombosis in GWAS or large multicenter studies, could reveal if additional molecular markers had a role in this peculiar clinical finding [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Barban et al [56], analyzing about 700,000 individuals, identified 12 loci associated with reproductive behavior highlighting also candidate genes and potentially causal variants [56]. Recently, Loizidou et al [57] assessed in a Ukainian cohort an association between 12 genetic loci and recurrent pregnancy loss [57]. In addition to the possibility to discover novel candidate genes and mutations, these GWASs on common genetic risk factors provide novel clues to interpret the underlying relationships and causality involved in the regulation of reproduction and fertility.…”
Section: Genetic Diseasesmentioning
confidence: 99%
“…Genetics now play an essential role in all stages of the reproductive path, from the diagnostic approach to the choice of more complex therapies: numerous research advances in genetics have increased reproductive medicine's success. For example, the rapid progress of the technologies applied to molecular diagnosis provides several diagnostic and screening options for the identification of genetic and chromosomal alterations related to infertility [1], non-syndromic infertility [2] or recurrent pregnancy loss [3]. However, while female infertility has been extensively investigated, only recently, attention is being paid to the etiological and pathophysiological causes related to male infertility.…”
mentioning
confidence: 99%